Transformation of Puskesmas Pelambuan: Analysis of LAFKI Accreditation Survey (Case Study) - Wahyudi, Ahyar; Nurhikmah, Hajjah; Aisyah, Siti; Nor, Rahmat Januar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community Health Centers (Puskesmas) play an important role in this context, as part of primary health care facilities. Community health centers must be able to provide quality basic health services and maintain the quality of these services. One strategy that can be used by Community Health Centers to achieve this goal is through the accreditation process. The aim of Puskesmas accreditation is to foster and improve the quality of service and safety for patients and the community on an ongoing basis. Accreditation is not just about getting a certificate, but more about a commitment to continuously improve the quality of health services provided to the community. The accreditation survey at the Pelambuan Community Health Center is an important effort to improve the quality of health services. This process involves surveyors conducting document checks and field searches to ensure that management, programs and clinical services comply with accreditation standards.